How the industrial journalist can promote good relations - Dirk Venter; Bosman Olivier (Communicare)
The industrial journalist has a basic responsibility to promote good relationships between employer and employee. Efficient two-way communication through the house journal is of vital interest to the modern company or organisation to ensure mutual understanding goodwill and appreciation. Managements must inform and motivate their employees at all times, drawing them closer to the heart of the company or organisation through messages conveyed by management supporting their job security, remuneration and recognition and increasing their insight and knowledge of the total work environment. Managements should also be susceptible to their fears or desires in the labour context, allowing the employee to express his views and opinions in a responsible, loyal fashion to his fellow-employees and to management. Silence in the work situation no longer implies consent.